Analisis Big Five Personality Dan Psychological Capital Terhadap Kinerja Pegawai Perusahaan XYZ - Marissa Puspa Dewi; Syamsul Hadi Senen (Jurnal Visi Manajemen, 2024)
This study aims to analyze the influence of Big five personality and Psychological capital on employee performance at XYZ Company, an educational institution. The research employs a descriptive quantitative method with path analysis using AMOS. The sample was randomly selected from all employees of XYZ Company. The results indicate that Big five personality and Psychological capital have a positive and significant impact on employee performance. The dimensions of conscientiousness and optimism contributed the most to performance improvement. This study provides critical implications for human resource management, particularly in designing strategies for personality development and psychological capital enhancement to boost organizational productivity.